KAJIAN PERANAN ISTRI NELAYAN TERHADAP PENDAPATAN KELUARGA DI KELURAHAN SUNGAI KAPIH KECAMATAN SAMBUTAN KOTA SAMARINDA - Kharisma; Qoriah Saleha; Muhammad Syafril (Jurnal Pembangunan Perikanan dan Agribisnis, 2020)
The research aimed to find out what productive activities a fisherman's wife does to increase family income, knowing how much a fisherman's wife contributed to family income and knowing what factors that affected the decision of a fisherman's wife to engage in productive activities. About 50 fishing families were taken as samples of research, sampling performed on Disproportionate Stratified Random Sampling. Analysis of the data in this study used quantitative descriptive analyses. Based on the analysis obtained the results that the productive activities carried by the wife of fishermen in the form of salted fish processing, fish crackers processing, sales of fresh fish, merchants, and service providers. The contribution of the fishermen's wife revenue to the fishermen family's income is still in a very low category of 19.31%. The influence of the factor in the decision of the fisherman's wife in the productive activity was the outpouring of productive work time. Keywords: The role of the Fisherman's wife, contributed to income, the Sungai Kapih district.